Pemuridan Paulus di Era Pandemi: Strategi Adaptasi Digital dan Implementasi di Perkantas Sulawesi Tengah - Lamau, Rino G.M.; Sunkudon, Pieter G.O.; Mertayasa, Nyoman (Sekolah Tinggi Teologi Injili Indonesia Palu, 2024)
This study explores the implementation of the Apostle Paul's discipleship principles in the Perkantas Central Sulawesi ministry during the COVID-19 pandemic. The pandemic disrupted many aspects of life, including church ministries, forcing a shift from in-person discipleship to digital platforms. This research aims to investigate how Small Group Leaders (PKK) adapted these discipleship strategies amidst the challenges posed by limited technology and virtual fatigue. Using a qualitative phenomenological approach, the study examines the experiences of six PKK members, highlighting their strategies and challenges in maintaining spiritual relationships and discipleship effectiveness. The results demonstrate that despite technical and relational difficulties, the discipleship process continued to thrive through digital innovations. The findings offer insights into how the Apostle Paul’s principles can be applied in contemporary crises, contributing to future discipleship strategies in similar situations.